Development and Validation of a Comic Tool: An Innovative Approach to Raise Awareness about Tobacco Control among School Teachers - Chaity Sarkar; Vikrant Mohanty; Aswini Y Balappanavar; Puneet Chahar; Kavita Rijhwani (Wolters Kluwer Medknow Publications, 2022)
Background: National legislation (COTPA) in India has focused on school children with dedicated section (6a and 6b) for tobacco control at Educational Institutions. Innovative mediums like Comic offer unique and engaging medium for dissemination of health information. However, its true potential remains unexplored in tobacco control. The study was conducted to develop and validate Comic for promotion of tobacco control laws in school settings. Materials and Methods: The present cross-sectional study was conducted among school teachers in Delhi in three phases: (1) need assessment, (2) development of Comic, and (3) validation (face/content validity by experts in public health/tobacco control, and construct validity by school teachers). Ethical clearance was obtained from Institutional Ethical Review Board. Prevalidated, structured, close-ended, and self-administered Questionnaire was used for the data collection. SPSS version 21 was used for descriptive and inferential results. Results: Phase 1 showed, out of 150 school teachers, 121 participated (80.66%). Mean age and teaching experience was 41.85 ± 9.76 years and 10.35 ± 6.53 years, respectively. Overall awareness about COTPA was 47.9% (n = 58) and COTPA sections 4 and 6 were 37.2% (n = 45). Majority 59.5% (n = 72) reported lack of access to training material. Phase 2 and 3 showed overall content validity index (CVI) score of 0.84. Construct validity evaluation from pre-postintervention yield mean ± SD scores of 3.94 ± 0.99 and 7.97 ± 1.17, respectively, (P < 0.001). Conclusion: Comic was developed on sound theoretical basis with satisfactory face, content and construct validity, to raise awareness about tobacco control among school children, and teachers to promote tobacco-free school.